Sistem Pengambilan Keputusan Penjurusan Akademik Sekolah Menengah Atas Berdasarkan Kemampuan Akademik, Potensi Psikologi dan Minat bakat Siswa Menggunakan Fuzzy Inference System Metode Sugeno Dua Lapis - Putra Rahmat Ramadhan; Giri Wahyu Wiriasto; Muhamad Syamsu Iqbal; Misbahuddin Misbahuddin (Teknik Informatika, 2019)
Fuzzy logic is a rule-based decision-making process that aims to solve a difficult problem and uncertainty. This research aims to develop a computer-based system which can assist in the decision maker to determine students’ academic major of senior high school based on their competence, psychology potential and talent-interest. The system is modeled using the fuzzy inference system with Sugeno inference method. The results show that the proposed system succeeds to provide recommendation subject in highly accurate, and it is more efficient than the manual decision-making process.